Women's adversities - Guimarães, Ana Paula (2020)
It is up to the State to promote appropriate measures to “guarantee fundamental rights and freedoms and the respect for the principles of a democratic law State”, in accordance with Article 9 (b) of the Constitution of the Portuguese Republic. [...]